Analisis Penerapan Sistem Keuangan Desa (SISKEUDES) Terhadap Kualitas Laporan Keuangan Tahun Anggaran 2022 di Desa Tales Kecamatan Ngadiluwih Kabupaten Kediri - Hamidah, Yuliana Siti; Ratih, Nur Rahmanti; Kusumaningarti, Miladiah (Peneliti.net, 2024)
The village financial system (SISKEUDES) provides space for village government agencies to obtain wider information and encourages them to play a role in conveying information. This system will make it easier for village governments to prepare village programs. With the increasingly difficult and complex tasks of village governments occurring in villages, information and communication systems support villages in implementing governance that produces transparent and accountable financial reports. The aim of this research is to find out the results of the analysis of the implementation of the village financial system (SISKEUDES) on the quality of financial reports in Tales Village, Ngadiluwih District, Kediri Regency. This research was conducted in Tales Village, Ngadiluwih District, Kediri Regency using primary data. The data analysis technique is qualitative data analysis. Based on the results of the analysis, it was found that accountability and transparency in the management of village financial reports in Tales Village used stages in accordance with the regulations of PERMENDAGRI no. 20 of 2018 starting from planning and budgeting, implementation, administration, reporting and accountability so that Tales Village can produce good quality financial reports and in accordance with applicable regulatory standards